2018
DOI: 10.3390/polym10010096
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antibacterial Polyglycidols: Relationship between Structure and Properties

Abstract: Antimicrobial polymers are an attractive alternative to low molecular weight biocides, because they are non-volatile, chemically stable, and can be used as non-releasing additives. Polymers with pendant quaternary ammonium groups and hydrophobic chains exhibit antimicrobial properties due to the electrostatic interaction between polymer and cell wall, and the membrane disruptive capabilities of the hydrophobic moiety. Herein, the synthesis of cationic-hydrophobic polyglycidols with varying structures by post-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It was reported that the surface antimicrobial properties were strongly affected by the ratios and distribution of cationic and hydrophobic functionalities, indicating that the post-polymerization reactions can not only enhance the surface antimicrobial functions but also modulate the antimicrobial ability. 46…”
Section: Surface Functionalization Methodsmentioning
confidence: 99%
“…It was reported that the surface antimicrobial properties were strongly affected by the ratios and distribution of cationic and hydrophobic functionalities, indicating that the post-polymerization reactions can not only enhance the surface antimicrobial functions but also modulate the antimicrobial ability. 46…”
Section: Surface Functionalization Methodsmentioning
confidence: 99%
“… 14–21 Therefore, it is of great significance to design and understand the relationships between structure and property for their further applications. 22–24 …”
Section: Introductionmentioning
confidence: 99%